PEMBERDAYAAN KELOMPOK DHARMA LAKSANA (PENYANDANG CACAT) MELALUI PELATIHAN KEWIRAUSAHAAN - . Komalawati (Seminar Nasional Aplikasi Iptek (SINAPTEK), 2019)
ABSTRAKDesa Wisata Kamasan terletak di Kecamatan Klungkung. Masyarakat sekitar adalah pembuat kerajinan perak, ukiran selongsong peluru, emas dan lukisan wayang tradisional. Masyarakat disekitar desa Kamasan rata-rata bermata pencaharian sebagai seniman lukis dan ukir, salah satu kelompok pengerajin yang ada di Desa Kamasan adalah Kelompok Dharma Laksana yang beranggotakan penyandang cacat. Permasalahan yang dihadapi selama ini diantaranya (1) Minimnya akses pemasaran untuk memasarkan produknya, (2) Memerlukan sarana promosi profesional untuk pemasaran produksinya mengingat hingga saat ini mereka tidak memiliki sistem pemasaran dan hanya menunggu pembeli saja, (3) Kelompok usaha Dharma Laksana membutuhkan pendampingan dalam berbagai hal pengembangan kelompok yg lebih professional, (4) Pengembangan sarana modal usaha yg akan di kelola sebagai modal simpan pinjam dalam kelompok, (5) Memerlukan peningkatan ketrampilan usaha dibidangnya masing- masing tidak hanya teknis produksi tetapi juga manajemen produksi, (6)Mereka masih buta hukum perdaganganKata Kunci : Pengeraji, disabilitas, KamasanABSTRACTKamasan tourism village is located in klungkung district. The beauty village of its arts in making silver, carving bullet casings, gold and traditional puppet paintings. In addition to carving, puppet paintings are also developed as ornaments on cloth in the form of flags, banners, ider-ider and parba which are complementary decorations in holy places (temples). The people around the village of kamasan have an average income as artists of painting and carving, one of the groups of craftsmen in the village of kamasan is the dharma laksana group which has members with disabilities. The problems faced so far include (1) lack of access to marketing to market their products, (2) require professional promotional facilities for marketing their products, considering that until now they did not have a marketing system and only waited for buyers, (3) dharma laksana business group needed assistance (4) development of business capital facilities that will be managed as savings and loan capital in groups, (5) requiring an increase in business skills in their respective fields not only in technical production but also in production management, (6) they are still blind to trade law (do not understand the applicable laws or trade laws), so they need assistance if there are large transactions or contracts.Keywords: balinese curving, disability, kamasan, balinese carving